Total knee arthroplasty with the cement endoprosthesis «motor sich epk-2» - Chorny, Vadim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Arthroplasty is one of the main methods in surgical treatment of osteoarthritis in the later stages when there was already significant joint destruction happend. Motor Sich JSC produces medical products for over 20 years. In 2002 there was created, and in 2005 was started serial production of the first and the sole domestic knee endoprosthesis. Objective: To study the first results of knee replacement by means of implants «Motor Sich EPK-2». Methods: The work is based on the results of treatment of 96 patients (69 women and 27 men aged 35 to 80 years) with gonarthrosis in stages III–IV. In all patients we performed primary knee replacement with preservation of the posterior crucial ligament using implants «Motor Sich EPK-2». All patients received intraoperative antibiotic therapy with cephalosporins. Outcomes were assessed in the period from 1 to 6 years with the help of clinical, radiological methods, and a scale «Knee Society Score» (KSS). Results: according to subjective assessment of treatment there were revealed 50.0 % excellent results; Good 43.3 %, and 6.7 % of patients noticed improvement. After a year or more after surgery in the operated joint flexion was 90° or more, and 89 % of the patients could walk without additional support. Complications that led to substitution of the endoprosthesis have took place in 4 cases — deep infection (1), instability of tibial (2) and femoral (1) components. Survival of endoprostheses in terms up to 6 years was about 96 %. Conclusion: as a result of using of the knee joint endoprosthesis «Motor Sich EPK-2» there were obtained positive results in 96 % of patients up to 6 years after surgery which indicates that the high efficiency of this construct in the treatment of patients with knee joint osteoarthrosis in stage III–IV.